Desain Kabinet Multifungsi untuk Ruang Sempit Apartemen - Khansa Vidyaprabha; Endro Tri Susanto; Nor Jayadi; Rahmawan D. Prasetya (Jurnal Desain Indonesia., 2022)
A cabinet is a storage that is considered effective and efficient because apart from being useful as a place to store various items, it adds aesthetic value to a space. The high demand for land for housing has led to vertical flats, like apartments. An apartment with a studio type has simply one room, where the only space with a section is in the bathroom. In this type of apartment, furniture with optimal function is needed because the space in a studio apartment is very minimal but still compact to maximize every available space. Multifunctional furniture is suitable for studio-type apartments because it has more value in both ergonomics and economics. This design creates a multifunctional cabinet with a retro theme suitable for residential needs with relatively limited space. It has various functions as a storage for cutlery needs and can transform into a dining table set equipped with folding stools for 2-4 people. The design used the four-phase Design Thinking method in the Double Diamond model, such as discover, define, develop, and deliver. The methods used in the design are qualitative and quantitative data analysis using questionnaires, documents, and literature studies.